Differential Expression of Inflammation-Related Genes in Down Syndrome Patients with or without Periodontal Disease - Baus-Domínguez, M.; Gómez-Díaz, R.; Torres-Lagares, D.; Corcuera-Flores, J. R.; Ruiz-Villandiego, J. C.; Machuca-Portillo, G.; Gutiérrez-Pérez, J. L.; Serrera-Figallo, M. A. (Mediators of Inflammation, 2019)
Aim. Aware that Down Syndrome patients present among their clinical characteristics impaired immunity, the aim of this study is to identify the statistically significant differences in inflammation-related gene expression by comparing Down Syndrome patients with Periodontal Disease (DS+PD+) with Down Syndrome patients without Periodontal Disease (DS+PD-), and their relationship with periodontitis as a chronic oral inflammatory clinical feature. Materials and Methods. Case study and controls on eleven Down Syndrome patients (DS+PD+ vs. DS+PD-). RNA was extracted from peripheral blood using a Qiagen PAXgene Blood miRNA Kit when performing an oral examination. A search for candidate genes (92 selected) was undertaken on the total genes obtained using a Scientific GeneChip® Scanner 3000 (Thermo Fisher Scientific) and Clariom S solutions for human, mouse, and rat chips, with more than 20,000 genes annotated for measuring expression levels. Results. Of the 92 inflammation-related genes taken initially, four genes showed a differential expression across both groups with a p value of <0.05 from the data obtained using RNA processing of the patient sample. Said genes were TNFSF13B (p=0.0448), ITGB2 (p=0.0033), ANXA3 (p=0.0479), and ANXA5 (p=0.016). Conclusions. There are differences in inflammation-related gene expression in Down Syndrome patients when comparing patients who present a state of chronic oral inflammation with patients with negative rates of periodontal disease.